Design and synthesis of aromatic polyesters bearing pendant clickable maleimide groups - Nagane, Samadhan S.; Kuhire, Sachin S.; Jadhav, Uday A.; Dhanmane, Sushilkumar A.; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2019)
A bisphenol bearing pendant maleimide group, namely, N-maleimidoethyl-3, 3-bis(4-hydroxyphenyl)-1-isobenzopyrrolidone (PPH-MA) was synthesized starting from phenolphthalein. Aromatic (co)polyesters bearing pendant maleimide groups were synthesized from PPH-MA and aromatic diacid chlorides, namely, isophthaloyl chloride (IPC), terephthaloyl chloride (TPC), and 50:50 mol % mixture of IPC and TPC by low temperature solution polycondensation technique. Copolyesters were also synthesized by polycondensation of different molar proportions of PPH-MA and bisphenol A with IPC. Inherent viscosities and number-average molecular weights of aromatic (co)polyesters were in the range of 0.52-0.97 dL/g and 20,200-32,800 g/mol, respectively indicating formation of medium to reasonably high-molecular-weight polymers. C-13 NMR spectral analysis of copolyesters revealed the formation of random copolymers. The 10% weight loss temperature of (co)polyesters was found in the range 470-484 degrees C, indicating their good thermal stability. A selected aromatic polyester bearing pendant maleimide groups was chemically modified via thiol-maleimide Michael addition reaction with two representative thiol compounds, namely, 4-chlorothiophenol and 1-adamantanethiol to yield post-modified polymers in a quantitative manner. Additionally, it was demonstrated that polyester containing pendant maleimide groups could be used to form insoluble crosslinked gel in the presence of a multifunctional thiol crosslinker. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 630-640
Keywords: crosslinking; maleimide group; modification; polyesters; thiol-maleimide